Proposta para otimização de protocolos de exames em tomografia computadorizada, visando a redução das doses de radiação dos pacientes - Cás, Elias Vergílio da (2011)
The challenge for professional physicists, doctors and technicians and to identify the limits of acceptable image quality of the procedures to minimize the radiation dose to patients subjected. The definition of image quality should extend to matters of view of lesions to optimize the dose of radiation. (Kalra et al, 2004, p. 620). In this paper, the proposed optimization of the protocols provided by manufacturers of equipment for computed tomography (CT), give yourself to the reduction of transportable cargo (MAS) suggested by the manufacturers. The proposed new MAS, or optimized to be found by the intersection of two curves, which correlate dose levels and noise, plotted on the y axis, with the MAS, the x-axis Two devices were studied with computed tomography protocols optimized. Equipment has a single section (single slice) and the other multiple sections (multi-slice). The optimization was carried out in the protocols correspond to the skull by larger percentages of examinations. The quality of images of original and optimized protocols was analyzed quantitatively and qualitatively. Quantitatively, we analyzed the relation to noise (ASD), the High Spatial Resolution Contrast (HSRC), the spatial resolution of low contrast (SRLC) and Signal to Noise Ratio (SNR). From a qualitative (images) analyzed the noise (phantom water), the HSRC (phantom) and SRLC (phantom). Concurrently, we estimated the amount of heat generated in the X-ray tube. For the protocol 1∆ original, but 250 mAs, the CTDIVol, Exp was 33.19. For the protocol 1∆ optimized for 235 mAs, the CTDIVol, Exp was 31.37. 2∆ for the original protocol, but in 250, the CTDIVol, Exp was 33.96. For the protocol optimized for 235 mAs, the CTDIVol, Exp was 32.96. For the protocol 3∆ original, but 150, the CTDIVol, Exp was 18.28. For the protocol 3∆ optimized for 143 MAS, the CTDIVol, Exp was 16.63. For the protocol 4∆ original, but 150, the CTDIVol, Teo was 39.90. For the protocol optimized 4∆, 135 mAs, the CTDIVol, Exp was 28.29. For protocol 5∆ original, but 380, the CTDIVol, Exp was 40.97. For protocol 5∆ optimized for 367 mAs, the CTDIVol, Teo was 44.66. For protocol 6∆ original of 190 mAs, the CTDIVol, Exp was 20.04. For protocol 6∆ optimized for 178 mAs, the CTDIVol, Exp was 18.66. The protocols were already with low mAs, the technique used to find the optimal mAs provided noise levels that have not harmed the image quality, there was a natural increase in noise with decreasing mAs, however, that amount was found acceptable, as can be seen in the images obtained.